Tie breaker. (Economist, 2016)
The author reflects on the European Union's (EU) case against internet search company Google Inc. He refers to the claim of EU division head Margrethe Vestager of Google's abuse and unfair dominance in control of the operating system Android. The author adds the European Commission claims that Google has dominated the European market share in internet search, licensed smartphone operating systems, and Android platform.